Learning about Time within the Spinal Cord II: Evidence that Temporal Regularity Is Encoded by a Spinal Oscillator - Lee, Kuan H.; Huang, Yung-Jen; Grau, James W. (Frontiers in Behavioral Neuroscience, 2016)
How a stimulus impacts spinal cord function depends upon temporal relations. When intermittent noxious stimulation (shock) is applied and the interval between shock pulses is varied (unpredictable), it induces a lasting alteration that inhibits adaptive learning. If the same stimulus is applied in a temporally regular (predictable) manner, the capacity to learn is preserved and a protective/restorative effect is engaged that counters the adverse effect of variable stimulation. Sensitivity to temporal relations implies a capacity to encode time. This study explores how spinal neurons discriminate variable and fixed spaced stimulation. Communication with the brain was blocked by means of a spinal transection and adaptive capacity was tested using an instrumental learning task. In this task, subjects must learn to maintain a hind limb in a flexed position to minimize shock exposure. To evaluate the possibility that a distinct class of afferent fibers provide a sensory cue for regularity, we manipulated the temporal relation between shocks given to two dermatomes (leg and tail). Evidence for timing emerged when the stimuli were applied in a coherent manner across dermatomes, implying that a central (spinal) process detects regularity. Next, we show that fixed spaced stimulation has a restorative effect when half the physical stimuli are randomly omitted, as long as the stimuli remain in phase, suggesting that stimulus regularity is encoded by an internal oscillator Research suggests that the oscillator that drives the tempo of stepping depends upon neurons within the rostral lumbar (L1-L2) region. Disrupting communication with the L1-L2 tissue by means of a L3 transection eliminated the restorative effect of fixed spaced stimulation. Implications of the results for step training and rehabilitation after injury are discussed.